The role of public research agencies in building agri-food bioscience impact and innovation capacity in sub-Saharan Africa: The challenge beyond science capability - Altshul, Helen J.; McMillan, Larelle; Hall, Andrew (Intellect, 2019)
Bioscience advances present important opportunities for economic development and sustainable intensification of African agriculture. In the global North, the private sector invests heavily in applied research, whereas in Africa the public sector shoulders the burden of developing research capacity. This article explores whether public science agencies should assume an expanded role to approach bioscience capacity using a system lens – developing capability for innovation within the whole system. The article identifies the types of intervention, beyond skills development, research infrastructure and funding that could enhance the potential of bioscience as an innovation driver. Following a summary of trends, a model of the system capacities required for bioscience impact and innovation is proposed and used to analyse a case study from East Africa. The results suggest that a fundamental rethink of the role of public science agencies within the wider biosciences landscape is required, necessitating complementary investments and a more complex network of partnerships across public and private sectors.